Penerapan model kooperatif tipe think-talk-write untuk meningkatkan kemampuan komunikasi matematik pada materi bangun datar segi empat di kelas VII SMP Negeri 8 Binjai - Anggraini, Dewi (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The aim of this research is to knowing how the strategy is the implementation of learning model Think-Talk-Write that can improve students ’mathematical communication, and know how to increase students’ mathematical communication. This research is a classroom action research. The research subject is class VII SMP Negeri 8 Binjai totaling 32 students. This research was conducted in two cycles. The difference in treatment in the first cycle and the second cycle lies in guiding the investigation stage. In the first cycle guided individually, while the second cycle guided individuals and groups. Each end of the given test cycle mathematical communication skills as much as 4 question. From the results of initial tests discovered that the average student mathematical communication skills 46.09 with the percentage of students who have reached the KKM amounted to 25% of total students. After administration of the action in the first cycle, the average math student communication skills increased to 64.25 with the percentage of students who achieve KKM amounted to 46.88% of the total number of students. After administration of the action on the second cycle, the average math student communication skills increased to 76.56 with the percentage of students who achieve KKM amounted to 81.25% of the total number of students. Based on these results it can be concluded that an increase in communication skills math class VII SMP Negeri 8 Binjai so learning by applying the learning model Think-Talk-Write can be used as an alternative learning mathematics to improve communication skills of students.